A confidential inquiry into asthma deaths in Wales. Issue 11 (1st November 1999) - Burr, M L; Davies, B H; Hoare, A; Jones, A; Williamson, I J; Holgate, S K; Arthurs, R; Hodges, I G C
Abstract : BACKGROUND: Death from asthma is regarded as preventable in principle, especially under the age of 65 years. METHODS: In 1994 a confidential inquiry was set up to investigate deaths attributable to asthma in residents of Wales under the age of 65 years. During the period of the inquiry 92 cases were notified as being ascribed to asthma, or (in 1996) having a mention of asthma on the death certificate. Of these, 80 were investigated further with the help of general practitioners, hospital notes, and relatives. The details were then considered by a small panel of doctors who endeavoured to identify factors that may have contributed to the deaths. RESULTS: Asthma was considered to be the underlying cause of 52 deaths. Although disease severity was usually a major factor, some aspect of the patient's behaviour or circumstances seemed to have contributed to 31 deaths, while in 15 cases there was probably a deficiency in medical care. CONCLUSIONS: Some preventable asthma deaths still occur, particularly in relation to inadequate treatment. Factors associated with patients' behaviour and circumstances are more difficult to tackle but, if doctors are aware of high risk patients, increased vigilance may prevent some deaths.